A nomenclatural and taxonomic review of the Campanulaceae described in Vellozo’s Flora Fluminensis - Rollim, Isis De Mello; Peres Coelho, Guilherme; Teresinha Sfoggia Miotto, Silvia; Ricardo Vieira Iganci, João; Trovó, Marcelo (Phytotaxa, 2023)
Species of the Campanulaceae described by Frei José Mariano da Conceição Vellozo in his Flora Fluminensis are revised. All of them were placed by Vellozo in the genus Lobelia; however, three names have been placed in the synonymy with other genera by previous revisions: L. fluminensis (= Siphocampylus fluminensis), L. ignea (= S. corymbifer), and L. purpurea (= Centropogon cornutus). The present work indicates L. alpina as a synonym of L. camporum. Among the species described by Vellozo, only L. fistulosa is currently accepted as a valid name, while L. ensiformis remains doubtful, not corresponding clearly to any known species. Five lectotypes are designated to clarify application of Vellozo’s names. Photos of the known species in situ are provided.